2005
DOI: 10.1021/jo050581g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Nucleophilic Substitution at Sulfur in Sulfinyl Derivatives

Abstract: A series of gas-phase nucleophilic substitution reactions at sulfur of methanesulfinyl derivatives by small anions (chloride, cyanide, hydroxide, methoxide, amide, and phosphide, identical to the leaving group in each case) were examined by Hartree-Fock, MP2, and DFT computations. In most cases, substitution was found to follow an addition-elimination mechanism, resulting in a triple-well potential energy surface with small barriers of activation on either side of the central, tetracoordinate-sulfur minimum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These bridges are often involved in or affected by, redox processes, in which a disulfide bond may interconvert with a dithiol system . Bachrach and co‐workers, highlighted other reaction mechanisms to achieve S−S bond cleavage. Their work was expanded on by Ramos, Bickelhaupt, and co‐workers ,.…”
Section: Variation Of Central Atommentioning
confidence: 99%
See 2 more Smart Citations
“…These bridges are often involved in or affected by, redox processes, in which a disulfide bond may interconvert with a dithiol system . Bachrach and co‐workers, highlighted other reaction mechanisms to achieve S−S bond cleavage. Their work was expanded on by Ramos, Bickelhaupt, and co‐workers ,.…”
Section: Variation Of Central Atommentioning
confidence: 99%
“…Orian and coworkers further investigated reactions involving other chalcogens by focusing on S N 2@S, S N 2@Se, and S N 2@Te . Bachrach and co‐workers studied simple acyclic also investigated cyclic sulfides, and sulfinyl derivatives . In the latter compounds, the additional oxygen ligand to sulfur does not have a marked effect on the energy surface and the reaction proceeds mainly through a triple‐well mechanism.…”
Section: Variation Of Central Atommentioning
confidence: 99%
See 1 more Smart Citation
“…7 In a recent study, this reaction was explored for the particular case of sulfinyl chlorides. 8 Um et al Reported, along with kinetic evidence for a stepwise mechanism, the first spectroscopic observation of an intermediate in the reaction of a sulfinate ester with NaOEt in anhydrous EtOH. 9 A study of the kinetics and mechanism THE SYNTHESIS OF SULFINYLPHTHALIMIDES AND THEIR REACTIONS 2251 of the acid catalyzed hydrolysis of a series of N-(p-substitutedarylsulfinyl)phthalimides have been studied in concentrated aqueous mineral acids in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The study on the chlorine displacement [19] revealed that the alcohol reacts directly with MeSOCl following an addition/elimination mechanism originally proposed by Bachrach. [20] The absolute configuration of sulfur is decided in the addition step, which involves a hydrogen transfer from the alcohol to the sulfinyl oxygen of the substrate. The base participates into the mecha- Table 1.…”
Section: Full Papersmentioning
confidence: 99%